A Study on the Image Uniformity According to Center-line Velocity in Digital Radiation System - Lee, Byeong-Jin; Lim, Cheong-Hwan; Jeong, Seung-Hun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Generally speaking, it is the case that there is an increase in diagnostic radiators are being examined without aligning the center-line, due to its movement constraint. Therefore, we would like to compare the uniformity of images according to the center-line velocity in the CR System and DR System.Methods/Statistical Analysis: The methods used in this study are to measure the uniformity of the images, as the images were acquired by preparing a 7x7x7(cm) hexagonal phantom with 3mm thick acrylic and adding water. As noted in the CR and DR systems, SID was measured at 150cm and 180cm, and the measurement condition was shown to be 50kVp and 4mAs for each one.Findings: The findings noted that the doses were shown to have a higher cathode value than the center value according to the Heel Effect of the radiation equipment, and were measured lower in the Anode. Although the SNR showed little change in location in the CR System, the difference between the Cathode and Anode in the DR system was more than 8%. In this context, the intensity distribution in this case was shown to show a large variation of the cathode and anode in the CR System with decreasing in the uniformity of the images. Also, it is noted that in the DR system, the uniformity of the image decreased due to a large variation in the anode.Improvements/Applications: In this case, the discordance of the center-line in the DR system was shown to have a large impact on the image and reduced uniformity. Overall in the process of the radiation test, it was analyzed that the degree of uniformity is excellent when the detector and center-line are accorded.